2021
DOI: 10.3389/fpsyt.2021.765485
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Polyphenol Supplementations on Improving Depression, Anxiety, and Quality of Life in Patients With Depression

Abstract: Background: Increased prevalence of mental disorders has become a significant public health concern. Recent studies have linked nutrition to depression and anxiety, suggesting that dietary changes or nutritional supplementation may be beneficial in improving mental disorders. Polyphenols have anti-inflammatory and antioxidant properties that may counteract physiological changes in depression and anxiety. This study examined the effectiveness of polyphenol supplementation in improving depression, anxiety and qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“… 131 However, as shown in this meta‐analysis, different types of polyphenols may have varying beneficial effects (improved fatigue and insomnia, or improvement of somatic symptoms), which suggests that different populations with depression may benefit from different polyphenols. 131 Polyphenols are also important candidates for adjunctive therapy to antidepressants as demonstrated in animal and clinical trials. For example, an adjunctive treatment with the polyphenolic compound curcumin for 12 weeks displayed significant improvements in depression rating scores in patients with MDD when combined with different antidepressants (i.e., fluoxetine, sertraline, mianserin, or trazodone).…”
Section: Adjunctive Lifestyle Factors: Targeting Inflammation Through...mentioning
confidence: 87%
See 2 more Smart Citations
“… 131 However, as shown in this meta‐analysis, different types of polyphenols may have varying beneficial effects (improved fatigue and insomnia, or improvement of somatic symptoms), which suggests that different populations with depression may benefit from different polyphenols. 131 Polyphenols are also important candidates for adjunctive therapy to antidepressants as demonstrated in animal and clinical trials. For example, an adjunctive treatment with the polyphenolic compound curcumin for 12 weeks displayed significant improvements in depression rating scores in patients with MDD when combined with different antidepressants (i.e., fluoxetine, sertraline, mianserin, or trazodone).…”
Section: Adjunctive Lifestyle Factors: Targeting Inflammation Through...mentioning
confidence: 87%
“…One of the most studied families of biomolecules for human health are polyphenols, which are phytochemicals found abundantly in plant food sources and characterized by the presence of multiple hydroxyl structural units on aromatic rings 130 . Indeed, a meta‐analysis including 18 studies ( n = 1,523) found that polyphenol supplementation has an overall positive impact on improving depression, anxiety, and quality‐of‐life parameters in patients with depression 131 . However, as shown in this meta‐analysis, different types of polyphenols may have varying beneficial effects (improved fatigue and insomnia, or improvement of somatic symptoms), which suggests that different populations with depression may benefit from different polyphenols 131 .…”
Section: Adjunctive Lifestyle Factors: Targeting Inflammation Through...mentioning
confidence: 99%
See 1 more Smart Citation
“…Compelling evidence has encouraged research into the complementary use of nutrition supplements plus dietary plans with the aim to impact the pathways implied in psychiatric disorders. Studies have also reported common dietary factors in the underlying processes of anxiety and depression; particularly diets or supplements that are high in antioxidants and anti-inflammatories (such as Vitamin C, Vitamin A, Polyphenol and beta-carotene) have shown an inverse relationship with depression and anxiety severity levels [24,25].…”
Section: Diet Intervention On Anxiety and Depressionmentioning
confidence: 99%
“…Increased oxidative stress and elevated inflammatory markers can trigger depressive symptoms [ 24 ]. According to randomized controlled research, antioxidant supplementation for 6 weeks significantly raised plasma antioxidant levels in depressed individuals and was linked to a considerable decrease in depressive symptoms [ 25 ]. Dietary polyphenols are a class of antioxidants that appear in a variety of antioxidant supplements and offer a range of physiological advantages that aid in the treatment of mental diseases.…”
Section: Introductionmentioning
confidence: 99%